THE ROLE OF THE PRINCIPAL IN STRENGTHENING THE RELIGIOUS CHARACTER VALUES OF STUDENTS AT SD AL ISLAM PENGKOL JEPARA - Munir, Muhammad Misbahul; Niswah, Nihlatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
One of the characteristics that must be instilled in students at the elementary school level is religious character. Religious character is the foundation for cultivating student character, where an excellent religious character can create moral human resources. Cultivating religious character cannot be separated from the role of the school principal. This research aims to analyze the role of SD Al Islam Pengkol Jepara's principal in strengthening students' religious character through the pillars of the Pancasila student profile of faith and devotion to God Almighty. The method used in this research is a descriptive qualitative case study type with data analysis techniques used, namely observation, interviews, and documentation. The research results show that school principals are essential in cultivating student character. In general, the program launched by the principal of SD Al Islam Pengkol Jepara is divided into three programs: class, habituation, and exemplary. The class program is filled with written Pegon, Diniyyah classes, and Islamic boarding school classes. The habituation program is filled with praying Dluha and Dzuhur in the congregation, praying and reading the Asmaul Husna before learning and getting used to shaking hands and kissing the teacher's hand. The exemplary programs carried out by school principals include exemplary religious character, exemplary disciplinary character, exemplary democratic character, and exemplary social care character.